2020
DOI: 10.12669/pjms.36.4.2031
|View full text |Cite
|
Sign up to set email alerts
|

qSOFA score for prediction of sepsis outcome in emergency department

Abstract: Objective: The third international consensus definition for sepsis and septic shock (sepsis 3) task force recently introduced qSOFA (quick sequential organ failure assessment) as a score for detection of patients at risk of sepsis outside of intensive care units. We performed this study to evaluate the validity of qSOFA for early detection and risk stratification of septic patients in emergency department. Methods: We conducted this study in an emergency department of the largest university affiliated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In 2016, the Third International Consensus Definition of Sepsis (Sepsis-3) defined sepsis as a ‘life-threatening organ dysfunction due to a dysregulated host response to infection’ 5. Indeed, organ dysfunction was found to have better ability to predict in-hospital mortality or to target patients with higher risk of adverse outcomes than the original Systemic Inflammatory Response Syndrome (SIRS) criteria and the previous Sepsis-2 definition 6–10. However, the successive changes in sepsis definition made it difficult to identify the true incidence of sepsis and to assess the variation in incidence over time and across countries 1 2…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the Third International Consensus Definition of Sepsis (Sepsis-3) defined sepsis as a ‘life-threatening organ dysfunction due to a dysregulated host response to infection’ 5. Indeed, organ dysfunction was found to have better ability to predict in-hospital mortality or to target patients with higher risk of adverse outcomes than the original Systemic Inflammatory Response Syndrome (SIRS) criteria and the previous Sepsis-2 definition 6–10. However, the successive changes in sepsis definition made it difficult to identify the true incidence of sepsis and to assess the variation in incidence over time and across countries 1 2…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the course of sepsis, clinical markers are needed to improve diagnosis and risk-adaptive treatment in critically ill patients. Besides clinical assessment and scores to evaluate organ failure [ 16 ], biomarkers may indicate patients at risk for unfavorable courses as well as impaired short- and long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of development of our protocol, the qSOFA was relatively new and was therefore selected primarily based on its feasibility in the TASH-ED setting, where lactate (recommended by many protocols as part of septic workup) is expensive and not routinely available and turnaround of laboratory results could lead to important delays in initiating care. Several studies conducted in LMICs have since found the qSOFA to have good predictive ability [ 35 , 40 ] and to reduce time to diagnosis [ 40 ]. Informal assessment of the application of qSOFA and accuracy of diagnosis in the first few months of implementation found the qSOFA was being appropriately applied, and that sepsis cases were being accurately captured.…”
Section: Discussionmentioning
confidence: 99%